2021
DOI: 10.1093/jas/skab356
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary leucine and tryptophan on serotonin metabolism and growth performance of growing pigs

Abstract: An experiment was conducted to test the hypothesis that increased dietary Trp is needed in high-Leu diets for growing pigs to prevent a drop in plasma serotonin and hypothalamic serotonin concentrations and to maintain growth performance of animals. A total of 144 growing pigs (initial weight: 28.2 ± 1.9 kg) were assigned to 9 treatments in a randomized complete block design with 2 blocks, 2 pigs per pen, and 8 replicate pens per treatment. The 9 diets were formulated in a 3 × 3 factorial with 3 levels of diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Similar to this work, at high Leu:Lys ratios, growth performance of weaned pigs was reduced. The effect of high Leu:Lys ratio when main protein sources are replaced with GDDY or other corn-fermented protein products ( Yang et al 2018a , Cemin et al 2021 ) has been well documented in growing-finishing pigs ( Rojo 2011 , Cemin et al 2019 , Clizer 2021 , Kwon et al 2022 ). It is suggested that in growing finishing pigs Leu:Lys ratios above 150% are expected to negatively impact performance ( Htoo et al 2014 , Cemin et al 2019 , Kwon et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to this work, at high Leu:Lys ratios, growth performance of weaned pigs was reduced. The effect of high Leu:Lys ratio when main protein sources are replaced with GDDY or other corn-fermented protein products ( Yang et al 2018a , Cemin et al 2021 ) has been well documented in growing-finishing pigs ( Rojo 2011 , Cemin et al 2019 , Clizer 2021 , Kwon et al 2022 ). It is suggested that in growing finishing pigs Leu:Lys ratios above 150% are expected to negatively impact performance ( Htoo et al 2014 , Cemin et al 2019 , Kwon et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, Leu supplementation did not significantly affect ADFI of growing pigs, probably because the coordination between small amounts of Leu, valine, isoleucine and tryptophan in the diet had no significant effect on the serotonin production by the hypothalamus. Most studies have focused on the effects of excessive Leu supplementation on hypothalamic serotonin release in piglets or growing pigs, but there are few studies on whether low levels of Leu supplementation promote serotonin release ( Kwon et al., 2019b , 2022 ; Wessels et al., 2016 ). Average backfat thickness, loin-eye area, lean meat percentage and total fat percentage are important indicators of carcass weight.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are no currently available GEMs for pigs; however, nutrition studies from whole animal production can provide insights into essential nutrients for cell culture. Animal science studies on pig metabolism have shown that lysine and tryptophan are limiting amino acids in swine diets and impact growth performance (Hasan et al., 2020; Kwon et al., 2022). Additionally, pig residual feed intake, a sensitive and accurate indicator of feed efficiency, is correlated to the expression of genes ( phosphatidylcholine:ceramide cholinephosphotransferase 1 [ SGMS1 ], phosphatase and tensin homolog [ PTEN ], arachidonate 12‐lipoxygenase, 12S type [ ALOX12 ], protein kinase Adenosine Monophosphate (AMP)‐ activated non‐catalytic subunit gamma 3 [ PRKAG3 ], 1‐phosphatidylinositol‐ 4,5‐bisphosphate phosphodiesterase delta‐4 [ PLCD4 ]) highly involved in porcine lipid metabolic processes (Do et al., 2014).…”
Section: Animals Of Interest To the Cultivated Meat Industrymentioning
confidence: 99%